Identification of Ethnoscience in Peringgesela Weaving as a Learning Resource for Environmental Chemistry - Al Idrus, Syarifa Wahidah; Rahmawati, Rahmawati; Sapitri, Riska Dia (Jurnal Pijar Mipa, 2025)
In the context of environmental chemistry learning, ethnoscience can be used to connect scientific concepts with cultural values. This learning helps students understand the importance of environmental conservation through a relevant and contextual approach. This study aims to identify the ethnoscience of Peringgesela weaving as a learning resource for Environmental Chemistry. The subjects of this study were Peringgesela weaving craftsmen. The research methods were observation, interview and documentation. The results showed that natural dyes such as tarum, mengkudu, and turmeric contain active compounds that represent chemical concepts such as redox reactions, acid-base, and extraction. In addition, the fixation process using synthetic fixation materials such as alum with the molecular formula KAl(SO4)2, lime Ca(OH)2 and tunjung (FeSO4) with waste that is directly disposed of in the surrounding waters. The absence of waste management shows the basic principles of environmental chemistry. The integration of ethnoscience in learning resources for Environmental Chemistry allows students to understand science concepts more contextually, relevantly, and deeply.